A bill to amend and render more effectual an act, made in the thirty-first year of the reign of his late Majesty, King George the second, intituled, "An act for the due making of bread, and to regulate the price and affize thereof, and to punish persons who shall adulterate meal flour or bread," etc ([London], 1797)
With: Minutes of the evidence taken before the Committee for council.